Challenges of Implementing Character Education Based on Islamic Values in the Independent Campus Learning Curriculum (MBKM) - Iqbal, Muhammad; Najmuddin, Najmuddin; Rizal, Muhammad; Zahriyanti, Zahriyanti (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2022)
Character education based on Islamic values ​​in the higher education curriculum is increasingly becoming an interesting topic of debate in contemporary education. This article aims to determine the challenges and opportunities faced in implementing character education based on Islamic values ​​in higher education, using qualitative methods through literature studies and searches. This research explores the concept of Islamic-based character education, analyzes the challenges faced in its implementation, and identifies opportunities to strengthen this approach in higher education curricula. The results of the analysis show that although there are various challenges, such as integrating Islamic values ​​into the secular curriculum, public perception of Islamic education, and limited resources, there are also significant opportunities, such as increasing awareness of the importance of character-based on Islamic values. education, support from Islamic educational institutions, and the important role of universities in shaping students' personalities and morals. These findings imply the need for a holistic and integrated approach to overcoming challenges and seizing opportunities to strengthen character education based on Islamic values ​​in higher education environments.